Terpenoid constituents of cinnamon and clove essential oils cause toxic effects and behavior repellency response on granary weevil, Sitophilus granarius - Plata-Rueda, Angelica; Campos, Juliana Mendonça; Rolim, Gabriela da Silva; Martínez, Luis Carlos; Santos, Marcelo Henrique Dos; Fernandes, Flávio Lemes; Serrão, José Eduardo; Zanuncio, José Cola (Ecotoxicology and Environmental Safety, 2018)
This study evaluated toxic effects, repellency and respiration rate caused by terpenoid constituents of cinnamon and clove essential oils and against Sitophilus granarius L. (Coleoptera: Curculionidae). The lethal concentrations (LC 50 and LC 90 ), repellent effect, and behavior repellency response on adults of S. granarius after exposure to six concentrations of each essential oil and terpenoids were evaluated. The chemical composition of the cinnamon oil was also determined and primary compounds were eugenol (10.5%), trans-3-caren-2-ol (10.2%), benzyl benzoate (9.99%), caryophyllene (9.34%), eugenyl acetate (7.71%), α-phellandrene (7.41%), and α-pinene (7.14%). In clove essential oil, the primary compounds were eugenol (27.1%), caryophyllene (24.5%), car- yophyllene oxide (18.3%), 2-propenoic acid (12.2%), α-humulene (10.8%), γ-cadinene (5.01%), and humulene oxide (4.84%). Cinnamon and clove essential oil was toxic to S. granarius. In toxic terpenoids compounds, eu- genol has stronger contact toxicity in S. granarius than caryophyllene oxide, followed by α-pinene, α-humulene, and α-phellandrene. Insects reduced their respiratory rates after being exposed to essential oil terpenoids and avoided or reduced their mobility on terpenoid-treated surfaces. Cinnamon and clove essential oil, and their terpenoid constituents were toxic and repellent to adult S. granarius and, therefore, have the potential to prevent or retard the development of insecticide resistance.
Keywords: Biopesticides; Gas chromatography; Insect resistance; Lethal effect; Pest control; Repellency